Miss Fisher's murder mysteries. [videorecording (DVD)] Series 1 - Davis, Essie; Page, Nathan, 1973-; Johnstone-Burt, Hugo; Greenwood, Kerry
Our lady sleuth sashays through the back lanes and jazz clubs of late 1920's Melbourne, fighting injustice with her pearl-handled pistol and her dagger sharp wit.